Chapter INTEREURISLAND: from Field Research to a Possible Model for Internationalizing University Social Responsibility Experiences - Andrian, Nicola (Studies on Adult Learning and Education, 2018)
The research aims to analyse and justifiably develop an innovative model for the internationalization of University social responsibility experiences through the international mobility of undergraduate students, with a combination of study and internships